Micellization: A new principle in the formation of biomolecular condensates - Yamazaki, Tomohiro; Yamamoto, Tetsuya; Hirose, Tetsuro (Frontiers in Molecular Biosciences, 2022)
Phase separation is a fundamental mechanism for compartmentalization in cells and leads to the formation of biomolecular condensates, generally containing various RNA molecules. RNAs are biomolecules that can serve as suitable scaffolds for biomolecular condensates and determine their forms and functions. Many studies have focused on biomolecular condensates formed by liquid-liquid phase separation (LLPS), one type of intracellular phase separation mechanism. We recently identified that paraspeckle nuclear bodies use an intracellular phase separation mechanism called micellization of block copolymers in their formation. The paraspeckles are scaffolded by NEAT1_2 long non-coding RNAs (lncRNAs) and their partner RNA-binding proteins (NEAT1_2 RNA-protein complexes [RNPs]). The NEAT1_2 RNPs act as block copolymers and the paraspeckles assemble through micellization. In LLPS, condensates grow without bound as long as components are available and typically have spherical shapes to minimize surface tension. In contrast, the size, shape, and internal morphology of the condensates are more strictly controlled in micellization. Here, we discuss the potential importance and future perspectives of micellization of block copolymers of RNPs in cells, including the construction of designer condensates with optimal internal organization, shape, and size according to design guidelines of block copolymers.